Optimization of essential oil-based natural disinfectants against Listeria monocytogenes and Escherichia coli biofilms formed on polypropylene surfaces - Vidács, Anita; Kerekes, Erika; Rajkó, Róbert; Petkovits, Tamás; Alharbi, Naiyf S.; Khaled, Jamal M.; Vágvölgyi, Csaba; Krisch, Judit (Journal of molecular liquids, 2018)
Polypropylene is frequently used in food contact applications, mainly for packaging or in food boxes to be used in microwave ovens. In this study, the biofilm elimination effect of selected essential oils (cinnamon, marjoram, and thyme) was evaluated against immature and mature biofilms of Escherichia coli and Listeria monocytogenes formed on polypropylene (PP) surfaces. The Response Surface Box-Behnken Design (BBD) with three variables and 17 assays was used to optimize concentration of essential oils (EOs) (1.1–15.8mg/mL), disinfection time (10min), and level of pH (4.5‐7.5) in the EO-based disinfection solutions. The optimized disinfectants were used against 24-, and 168-hour old biofilms formed on PP surfaces, and were successful in elimination of immature and mature biofilms, except cinnamon EO for E. coli where biofilms were destroyed only partially. The disinfectant effect of the EO-based natural solutions was in most cases equivalent or better compared to the per-acetic acid-based chemical sanitizer used in food industry or to sodium hypochlorite. •Concentration, acting time and pH of essential oil based disinfectants was optimized.•The disinfectants were used against E. coli and L. monocytogenes biofilms.•Immature and mature biofilms were eliminated from polypropylene surfaces.•EO based disinfectants were equivalent to industrial sanitizers.